2021
DOI: 10.1111/dth.14738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet‐rich plasma on the outcome of mini‐punch grafting procedure in localized stable vitiligo: Clinical evaluation and relation to lesional basic fibroblast growth factor

Abstract: Surgical methods are favorably used for treatment of stable vitiligo, and platelet-rich plasma (PRP) can be added to augment the effect. The additive value of PRP, however, remains elusive. Basic fibroblast growth factor (bFGF) is released from activated platelets with a capacity for stimulating melanocyte proliferation and migration. The treatment outcomes for the mini-punch grafting (MPG)/phototherapy treatment with and without PRP were assessed and the relation between bFGF and the obtained results were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…These results are in accordance with the study by Khan et al [47], where a simultaneous increase in both proliferation and differentiation of ADSCs were obtained when VEGF-A165 was combined with FGF-2. In general, our results are in line with all studies, in which FGF-2 is used for expansion of various cell types, such as mesenchymal stem cells including ADSCs [17], induced pluripotent stem cells [19] or chondrocytes [18], or for various regenerative therapies, in which the cell proliferation is needed, such as healing of cutaneous wounds [20,21], regeneration of damaged or diseased bone tissue [22,24], or treatment of vitiligo, requiring proliferation of melanocytes [26].…”
Section: Number Of Cells In Media With Growth Factorssupporting
confidence: 86%
See 1 more Smart Citation
“…These results are in accordance with the study by Khan et al [47], where a simultaneous increase in both proliferation and differentiation of ADSCs were obtained when VEGF-A165 was combined with FGF-2. In general, our results are in line with all studies, in which FGF-2 is used for expansion of various cell types, such as mesenchymal stem cells including ADSCs [17], induced pluripotent stem cells [19] or chondrocytes [18], or for various regenerative therapies, in which the cell proliferation is needed, such as healing of cutaneous wounds [20,21], regeneration of damaged or diseased bone tissue [22,24], or treatment of vitiligo, requiring proliferation of melanocytes [26].…”
Section: Number Of Cells In Media With Growth Factorssupporting
confidence: 86%
“…FGF-2 has been widely applied in clinical practice, particularly in cutaneous wound healing, such as second-degree burns and chronic ulcers [20,21], and in bone regenerative therapies, such as treatment of bone fractures, osteotomies, and osteonecrosis (for a review, see [22]), or treatment of periodontitis with intrabony defects ( [23]; for a review, see [24]). FGF-2 also proved its efficacy in the treatment of oral lichen planus [25] or vitiligo [26]. Animal studies also proved that FGF-2 is promising for regenerative therapy of spinal cord injury [27], of liver injury and liver diseases [28], or for treatment of alopecia [29].…”
Section: Introductionmentioning
confidence: 95%
“…A high concentration of growth factors is released from platelets due to secretion of alpha granules 10 min after activation 3,6,7 (platelet‐derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor‐beta (TGF‐ β), basic fibroblast growth factor (b‐FGF), and insulin growth factor (IGF)) 8–11 …”
Section: Discussionmentioning
confidence: 99%
“…These multiple factors lead to the migration of melanocytes from peri‐lesional skin, thus allowing repigmentation 13–16 . Basic fibroblast growth factor (b‐FGF) enhances melanocyte migration, keratinocyte, and fibroblast proliferation 8 . The response for TGF‐β is better if vitiligo is stable 17 .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs could thus be a promising method for the treatment of vitiligo [ 64 ]. Some studies have found that basic fibroblast growth factor promotes melanocyte migration and cytoskeletal rearrangements through PI3K/Akt and ERK signaling pathways, which might have certain clinical application value in melanocyte transplantation [ 65 , 66 ].…”
Section: Oxidative Stress and Vitiligomentioning
confidence: 99%